Contamination of fee-fishing ponds with agrochemicals used in sugarcane crops - Silva Santarossa, Maria A. da [UNESP]; Coleone, Ana C. [UNESP]; Mello, Nicoli P. de [UNESP]; Ignacio, Naiara F. [UNESP]; Machado, Angela A. [UNESP]; Marques Silva, Jose R. [UNESP]; Velini, Edivaldo D. [UNESP]; Machado Neto, Joaquim G. [UNESP] (Springer, 2020)
The increasing use of agrochemicals negatively affects the environment while the generated residues impact the hydrographic networks which feed the rivers and fishing ponds, so this work investigates pesticide contamination in the supply and fishing tank waters and bottom sediment of fee-fishing ponds located in micro-basins planted with sugarcane. The results are expected to indicate the water contamination level and the impact on both the environment and human health. Therefore, water and bottom sediments from fishing ponds nearby sugarcane plantations were sampled quarterly over a year. The pesticide residues in the samples were determined by high-performance liquid chromatography coupled to mass spectrometry. The contaminants detected in the ponds were tebuthiuron (2.908 ng mL(-1)), metolachlor (1.211 ng mL(-1)), hexazinone (1.065 ng mL(-1)), atrazine (1.008 ng mL(-1)), ametryn (1.004 ng mL(-1)), and clomazone (0.858 ng mL(-1)) in the water samples while metolachlor (2.308 ng g(-1)), tebuthiuron (0.540 ng g(-1)), hexazinone (0.394 ng g(-1)), and isoxaflutole (0.004 ng g(-1)) were detected in the sediment samples. Additionally, the results show that the size of sugarcane cultivated area nearby the fishing ponds, herbicide physicochemical parameters, and applications coinciding with high rainfall are all relevant factors for water contamination. Furthermore, sediment contamination is directly correlated with the herbicides in the water ponds.
Keywords: Affluent; Aquaculture venture; Fish tanks; Herbicides; Water contamination